Engineering properties of concrete made from gravels obtained in Southwestern Nigeria. Issue 1 (1st January 2017) - Sulymon, Nurain; Ofuyatan, Olatokunbo; Adeoye, Olowofoyeku; Olawale, Simon; Busari, Ayobami; Bamigboye, Gideon; Jolayemi, Joshua
Abstract: This study investigates the engineering properties of concrete produced from gravels and also verify the suitability of local gravel aggregates obtained from Southwestern Nigeria in place of crushed granite. Preliminary investigations were carried out in five selected states (Ogun, Oyo, Osun, Ondo and Ekiti) in Southwestern Nigeria to determine the registered gravel mining pits. Fifteen gravel mining pits based on age and scale of mining operations were selected for this study. Appropriate gravel constituents in concrete mix were determined using Gs factor. Concrete cubes 150 mm, 150 × 300 mm 2 cylinder modes and 150 × 150 × 750 mm 3 beams were cast with collected gravel. 1:2:4 mix ratio was employed. Sieves analysis, density, water absorption were carried out on aggregates, while compressive, flexural and split-tensile strengths of the concrete were determined for 28 days using ASTM and BS methods. High concrete strengths resulted from high FM, low AAV and average Gs of gravels. Gravel location with highest compressive, flexural and split-tensile strengths of concretes had 24.8, 3.5 and 2.8 N/mm 2 satisfying the minimum requirement of BS 811:1997 while that with lowest strengths had 9.6, 2.2 and 1.7 N/mm 2, respectively. Sources of gravel highly influence compressive, flexural and split-tensile strengths of the cubes and beams.